Online access to male factor infertility care: the challenge of finding a specialist - Arighno Das, M.D; Anne Darves-Bornoz, M.D; Tejas Joshi, M.S; Mary Kate Keeter, M.P.H; James M. Wren, M.D; Nelson E. Bennett, M.D; Robert E. Brannigan, M.D; Joshua A. Halpern, M.D (Elsevier, 2020)
Objective: To investigate internet search results available to couples searching for a male factor infertility specialist. Design: Cross-sectional. Setting: Online search engine. Patient(s): The phrase "male infertility specialist <state>" was searched in Google for 50 states and Washington D.C. The top 10 results (i.e., first page) of each search were evaluated for website content. Intervention(s): None. Main Outcome Measure(s): The first page of each search was evaluated for provider type (urology vs. obstetrics and gynecology), level of training (fellowship vs. none), male factor fertility information provided, and procedures offered. We compared search position rank (1-10) to determine the likelihood of finding an urologist versus a practitioner in obstetrics and gynecology. Result(s): A total of 419 results were identified; the majority were obstetrics and gynecology-related (N = 229, 54.7%). Urology-related results appeared higher than obstetrics and gynecology-related results (median, 4 vs. 5). Andrology fellowship-trained urologists were identified in 153 (36.5%) results. Among 229 obstetrics and gynecology results, 152 unique practices were identified. A small portion (N = 38, 16.6%) of these practices had a fellowship-trained urologist identified on the website. Most obstetrics and gynecology websites did not mention vasectomy reversal (N = 116, 76.3%) or varicocele repair (N = 93, 61.2%). A minority of practices offered referral to urologists for sperm extraction (N = 23, 15.1%) or offered sperm retrieval themselves (N = 23, 15.1%). Conclusion(s): When searching online for a male factor infertility specialist, most results identified obstetrics and gynecology physicians. A large proportion of obstetrics and gynecology websites lacked information on male factor fertility treatments and did not offer these treatments. These data indicate the need for a more robust online presence of male reproductive urologists to optimize online access.